2007
DOI: 10.1080/03602530701468391
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the 17α-Hydroxylase/C17,20-Lyase Activities of Porcine, Guinea Pig and Bovine P450c17 Using Purified Recombinant Fusion Proteins Containing P450c17 Linked to NADPH-P450 Reductase

Abstract: The cDNAs for cytochrome P450c17 (P450c17) of three species, pig, guinea pig, and cow, representing three families of mammals (suidae, procaviidae, and bovidae, respectively) were each engineered into an expression plasmid (pCWori+). The P450c17 domain of the coding sequence was connected to a truncated form of rat NADPH-P450 reductase by a linker sequence encoding two amino acids (SerThr). These fusion proteins were expressed in E. coli and purified for use in enzymatic assays to determine similarities and di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 75 publications
0
18
0
1
Order By: Relevance
“…The capacity of b5 to stimulate P450c17 appears to be well conserved, and the protein conserved enough to cross species. The 17,20-lyase activity of recombinant human P450c17 was stimulated by rat (19) as well as porcine (18) b5, and rat b5 can similarly support the bovine, porcine, and guinea pig P450c17 enzymes (37). The age-related decline in circulating adrenal androgen concentrations (41) is accompanied by a decrease in adrenal b5 expression (42).…”
Section: Discussionmentioning
confidence: 96%
“…The capacity of b5 to stimulate P450c17 appears to be well conserved, and the protein conserved enough to cross species. The 17,20-lyase activity of recombinant human P450c17 was stimulated by rat (19) as well as porcine (18) b5, and rat b5 can similarly support the bovine, porcine, and guinea pig P450c17 enzymes (37). The age-related decline in circulating adrenal androgen concentrations (41) is accompanied by a decrease in adrenal b5 expression (42).…”
Section: Discussionmentioning
confidence: 96%
“…The central importance of cytochrome b5 in supporting androgen synthesis by P450c17, and its significance as a functional marker of ZR maturation and androgen production (Sakai et al 1993, Yanase et al 1998, is supported by many elegant biochemical studies from a number of laboratories that have demonstrated its effects on recombinant P450c17 protein activity (Katagiri et al 1995, Lee-Robichaud et al 1995, Auchus et al 1998, Brock & Waterman 1999, Soucy & Luu-The 2000, Shet et al 2007). Specifically, cytochrome b5 selectively augments the 17,20-lyase activity of P450c17 that cleaves the pregnane to an androgen in the last committed step.…”
Section: Biochemical Adrenarchementioning
confidence: 90%
“…Cows and sheep are closer to humans in terms of steroid biosynthesis regulation, yet there are still some limitations. Ovine and bovine CYP17 do show relative delta 4 lyase deficiency yet their CYP17 also has a greater ability to hydroxylate progesterone with even a substrate preference for progesterone over pregnenolone (Estabrook et al 1991, Waterman et al 1993, Shet et al 1994, Swart et al 2003, Shet et al 2007). The expression of an abundance of CYP17 and HSD3B2 in the zona fasciculata still favors cortisol production over corticosterone Bovine (Ishimura and Fujita 1997, ovine Tangalakis et al 1990, Bird et al 1996).…”
Section: Requirements For Adrenal C19 Steroid Productionmentioning
confidence: 99%